Strategi Public Relation Dalam Menjaga Eksistensi Lembaga Pendidikan Islam Di Era Milenial - Aldo Redho Syam (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2019)
Public relations is one part of Islamic education institutions that are planned and deliberately formed to foster and develop Islamic education institutions continue to get the response and sympathy of the people who have a direct interest in Islamic educational institutions. Thus, the development of public relations in the millennial era is very much needed in maintaining the existence of Islamic education institutions, especially competition between educational institutions is very tight and competitive. And by developing public relations, it is expected to be able to achieve the goal of a relationship between Islamic education institutions and a harmonious society and can improve the educational process in Islamic educational institutions in a productive, effective, and efficient manner, so as to produce quality graduates.